Roles Of Cyclic Nucleotides In The Inhibition Of Platelet Function By Nitroprusside And By Ascorbate - Davidson, M M L; Haslam, R J (Thrombosis and Haemostasis, 1981)
The effects of nitroprusside and of ascorbate on the collagen-induced aggregation of washed human platelets and on the associated release of dense granule constituents were correlated with their effects on platelet cyclic GMP and cyclic AMP, which were measured either by radioimmunoassays or prelabelling methods. Nitroprusside at concentrations from 1 to 400 μM increased platelet cyclic GMP from 6 to 100-fold (maximum value approx. 50 pmol/109 platelets) and at concentrations above 10 μM also increased cyclic AMP about 2-fold (maximum value approx. 36 pmol/109 platelets). Platelet cyclic GMP reached a peak after an incubation period inversely related to the nitroprusside concentration and then declined. Collagen, which increased platelet cyclic GMP about 2-fold, enhanced the effect of nitroprusside on cyclic GMP but not cyclic AMP. Freshly prepared ascorbate (10 mM) increased platelet cyclic GMP about 8-fold. Storage of the ascorbate at pH 7 or simultaneous addition of 5 μM CuCl2 potentiated its action to give 15 to 20-fold increases in cyclic GMP and small increases in cyclic AMP. The results suggested that oxidation of the ascorbate was involved in these effects. In all the above studies, increases in platelet cyclic GMP greater than 6 to 10-fold were associated with measurable increases in cyclic AMP and with inhibitions of collagen-induced platelet responses that roughly correlated with the cyclic nucleotide changes. Addition of 100 μM 2',5'-dideoxyadenosine (an inhibitor of adenylate cyclase) blocked increases in platelet cyclic AMP but did not affect increases in cyclic GMP; this compound also decreased (but did not abolish) the inhibitory effects of nitroprusside and of ascorbate + CuCl2 These findings suggested roles for both cyclic GMP and cyclic AMP in mediating the inhibitions of platelet function by nitroprusside and ascorbate.